Museum Restitutions are More Than Just the Sum of Their Numbers - Lynda Albertson (Les Carnets de l’ACoSt)
In total, some 27 illegally-acquired artefacts have been confiscated in the last year from The Metropolitan Museum of Art by the Manhattan District Attorney’s Office, including a Tanagra-type figurine.